The effect of eight weeks of core stability training on the lower extremity joints moment during single-leg drop landing - FARAJ FATAHI; GHOLAMALI GHASEMI; MOHAMADTAGHI KARIMI; RAMIN BEYRANVAND (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2019)
Background: ‪Biomechanical factors are the main mechanism of load applied on the anterior cruciate ligament (ACL). The aim of this study was to evaluate the effect of eight weeks of core stability training on the lower extremity joints moment during a single leg drop landing task. Material and methods: ‪Thirty basketball athletes were randomly assigned into training and control groups. The training group performed core stability training for 8 weeks, but the control group did not perform these exercises. Lower extremity kinetics and kinematics variables during a single leg drop landing test were collected by a motion analysis system and a force plate in a pre- and post-test. Data were analyzed using a mixed repeated measure ANOVA test (p ≤ 0.05). Results: ‪The results showed there was a significant reduction in the moment of flexion, adduction and rotation of the hip and the moment of the knee and subtalar joint in the training group (p < 0.05), while there was no significant reduction in the ankle moment (p > 0.05). Conclusions: ‪Core stability training that was used in this study can reduce the forces exerted on the lower extremity joints during single leg drop landing. So, this study provides evidence that core stability training reduces lower extremity joints moment and may reduce the risk of ACL injury in athletes.